Pilkada in the Midst of Pandemic: A Case Study of Decreasing the level Community Political Participation in Sleman Regency Pilkada 2020 - Dewi, Nevy Rusmarina; Najib, Isnun (Indonesian Journal of Political Studies, 2022)
Since the March 2020 Pandemic that hit Indonesia, this condition has greatly impacted various aspects of life. Not only economic and social, but also in the political field, including the process of implementing democracy through the 2020 simultaneous regional elections. One of the regions that will hold the December 2020 elections is Sleman Regency. Political participation in the 2020 Pilkada in Sleman has decreased compared to political participation in the 2019 election. In the 2020 Pilkada it only reached 75.82%, while in the 2019 Election it could reach 87.7%. PAN. The ongoing Covid-19 pandemic is one of the main factors causing the decline in voter turnout. This study aims to determine the factors that influence the decrease in the level of community participation in the 2020 Pilkada during the pandemic condition in Sleman Regency. This research uses a qualitative approach with a literature study method. The results of this study indicate that the decline in the level of community participation in the 2020 Pilkada in Sleman Regency is influenced by several factors, among others, the first is the Covid-19 pandemic condition where not all residents registered in the DPT can participate in voting due to constraints on domicile outside the region with PPKM rules that apply. enforced by the government. Second, there is insufficient information and socialization related to the Pilkada and health protocols for preventing Covid-19 that were enforced during the Pilkada